Dynamics of neurovegetative regulation in children with recurrent upper respiratory tract infections and reduced myocardial functional reserve after the rehabilitation program - D.N. Sheludko; L.S. Ovcharenko (Zaslavsky O.Yu., 2018)
Background. Recently, problems with the level of children's health cause fears from both the medical and pedagogical community. The intensive school curriculum, the high infectious burden on the younger schoolchild's organism and increased interest to gadgets all lead to a strain on the functioning of the autonomic nervous system (ANS) and, consequently, to a reduced myocardial functional reserve. In connection with this, it was proposed to conduct recreational summer activities, the purpose of which was to have a restorative effect on the functioning of the ANS and the state of the myocardial functional reserve in the younger schoolchild. The objective was to analyze the clinical effectiveness of the medical rehabilitation program in children with recurrent upper respiratory tract infection (URTI) and with a reduced myocardial functional reserve. Materials and methods. Thirty younger schoolchildren were rehabilitated during a month. The clinical effectiveness of the rehabilitation program was evaluated according to the state of the ANS, parameters of regulatory system activity (PRSA), levels of neurotransmitters in the blood serum. The myocardial functional reserve was assessed. Results. Based on the results of the rehabilitation program, reliable results of improved ANS functioning were obtained: manifestations of sympathicotonia decreased, as well as the incidence of impaired PRSA and failure of adaptation processes (p < 0.05). A statistically significant decrease in the serum concentration of substance P, final stable nitric oxide metabolites and an increase in serum concentration of vasoactive intestinal peptide are noteworthy. This positive dynamics was accompanied by a significant decrease in the incidence of sympathicotonia, a rigid rhythm, disturbed PRSA, failure of adaptation processes (p < 0.05). The rehabilitation program led to an improvement in the results of the Ruffier test by 4 points compared to the indicators at the end of the school year. Conclusions. Carrying out a rehabilitation program in children with recurrent URTI and reduced myocardial functional reserve improved the indicators of the functional state of ANS and PRSA. Improvement of the functional state of the ANS and PRSA was accompanied by normalization (decrease or increase) of substance P, final stable nitric oxide metabolites, vasoactive intestinal peptide. Conducting the health-improving course in children with recurrent URTI and reduced myocardial functional reserve allowed decreasing the Ruffier test score by 4 points, which indicates an increase in the myocardial functional reserve.